Daya Hambat Ekstrak Buah Okra (Abelmoschus esculentus L.) terhadap Pertumbuhan Candida albicans - Iflachiana, Usykuri Naila; Dewi, Leni Rokhma; Prihanti, Ayu Mashartini (Fakultas Kedokteran Gigi Universitas Jember, 2024)
Oral candidiasis is a fungal infection of the superficial epithelium of the oral cavity caused by an overgrowth of Candida species. Effective therapy for oral candidiasis is nystatin. However, this drug has a variety of side effects. Therefore, natural therapeutic agent with minimal side effects is needed to be safe in long-term use. Okra fruit contains active ingredients that can be used as an antifungal agent. Aims to prove the ability of okra fruit extract and analyze the optimal concentration of okra fruit extract in inhibitting the growth of C. albicans. The antifungal activity test was carried out using the disk diffusion method. The research sample was divided into six groups, namely K (+) (nystatin), K (-) (DMSO 10%), and okra fruit extract with concentrations of 100%, 75%, 50%, and 25% obtained through the maceration process. Each research group was taken with a micropipette and then dripped on a paper disk. Paper disks were placed and distributed evenly on the surface of Saboroud Dextrose Agar (SDA) media that had been inoculated with C. albicans then incubated for 48 hours. The results showed the formation of a clear area around the paper disk that has been dropped with concentrations of 100%, 75%, and 50% of okra fruit extract. Okra fruit extract had an inhibitory effect on the growth of C. albicans and 100% concentration of okra fruit extract had the optimal ability to inhibit the growth of C. albicans.